2020
DOI: 10.1002/zaac.202000144
|View full text |Cite
|
Sign up to set email alerts
|

Chirality and Magnetic Properties of One‐dimensional Ln (Ln = Gd, Dy) Polymers

Abstract: The usage of the achiral ligand, in lanthanide chemistry, successfully obtained two series of chiral lanthanide complexes, formulated dand l-{Gd[IN][HIN][CH 2 OCH 2 O]} n (abbreviated as Gd) and dand l-{Dy[IN][HIN][CH 2 OCH 2 O]} n (abbreviated as Dy, HIN = isonicotinic acid). Crystallographic researches determined that four compounds are all one-dimensional (1D) chain structures and crystallized in a chiral space group. In addition, CH 2 OHCH 2 OH acts as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…49 Magnetic studies showed that complex 12 displayed ferromagnetic behaviour and a significant cryogenic MCE with a maximum −ΔS m,max value of 22.50 J kg (13) by using the achiral isonicotinic acid (HIN) . 50 Magnetically, complex 13 showed antiferromagnetic behaviour and a significant MCE with −ΔS m,max = 26.20 J kg −1 K −1 at 2.5 K for ΔH = 7 T. Similar to complex 10, formic acid was used as a ligand, Evangelisti et al reported a dense MOF Gd(HCOO) 3 (14). It exhibited a large MCE with −ΔS m,max = 55.90 J kg −1 K −1 , 14 which was very close to the −ΔS m,max value of complex 10.…”
Section: Monocarboxylate Ligandsmentioning
confidence: 99%
“…49 Magnetic studies showed that complex 12 displayed ferromagnetic behaviour and a significant cryogenic MCE with a maximum −ΔS m,max value of 22.50 J kg (13) by using the achiral isonicotinic acid (HIN) . 50 Magnetically, complex 13 showed antiferromagnetic behaviour and a significant MCE with −ΔS m,max = 26.20 J kg −1 K −1 at 2.5 K for ΔH = 7 T. Similar to complex 10, formic acid was used as a ligand, Evangelisti et al reported a dense MOF Gd(HCOO) 3 (14). It exhibited a large MCE with −ΔS m,max = 55.90 J kg −1 K −1 , 14 which was very close to the −ΔS m,max value of complex 10.…”
Section: Monocarboxylate Ligandsmentioning
confidence: 99%